Cell surface effects of human immunodeficiency virus - Garry, Robert F. (Biosci Rep, 1988)
Cell killing by human immunodeficiency virus (HIV) is thought to contribute to many of the defects of the acquired immunodeficiency syndrome (AIDS). Two types of cytopathology are observed in HIV-infected cultured cells: cell-cell fusion and killing of single cells. Both killing processes appear to involve cell surface effects of HIV. A model is proposed for the HIV-mediated cell surface processes which could result in cell-cell fusion and single cell killing. The purpose of this model is to define the potential roles of individual viral envelope and cell surface molecules in cell killing processes and to identify alternative routes to the establishment of persistently-infected cells. Elucidation of HIV-induced cell surface effects may provide the basis for a rational approach to the design of antiviral agents which are selective for HIV-infected cells.